How Important is Access to Jobs? Old Question - Improved Answer - Olof Aslund; John Osth; Yves Zenou (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2009)
We study the impact of job proximity on individual employment and earnings. The analysis exploits a Swedish refugee dispersal policy to obtain exogenous variation in individual locations. Using very detailed data on the exact location of all residences and workplaces in Sweden, we find that having been placed in a location with poor job access in 1990-91 adversely affected employment in 1999. Doubling the number of jobs in the initial location in 1990-91 is associated with 2.9 percentage points higher employment probability in 1999. Considering that the 1999 employment rate was 43 percent among the refugees, this is a considerable effect. The analysis suggests that residential sorting leads to underestimation of the impact of job access.
Keywords: J15; J18; R23; 330; Job access; endogenous location; natural experiment